The Effect of Regional Original Revenue and Special Allocation Funds on the Financial Performance of the Regional Government of Gorontalo Province in 2020-2025 - Lervia Mahwada Musa; Harun Blongkod; Ayu Rakhma Wuryandini (Economics and Digital Business Review, 2026)
This study aims to determine the influence of Regional Original Revenue (PAD) and Special Allocation Funds (DAK) on the Financial Performance of the Regional Government of Gorontalo Province in 2020–2025. This study uses a quantitative method with secondary data obtained from the Budget Realization Report (LRA) and local government financial statements published by the local government in Gorontalo Province. The sampling technique uses the saturated sample method, namely all districts/cities and the Gorontalo Provincial government that meet the research criteria during the 2020–2025 period. The data analysis technique used was multiple linear regression analysis with the help of the Statistical Package for the Social Sciences (SPSS) program. Based on the results of the study, it is shown that Regional Original Revenue has a positive and significant effect on the Financial Performance of Regional Governments. Special Allocation Funds affect the Financial Performance of Regional Governments. Simultaneously, Regional Original Revenue and Special Allocation Funds have a significant effect on the Financial Performance of the Regional Government of Gorontalo Province in 2020–2025.